An exploratory study on English Language proficiency and academic performance in the context of globalization of accounting education / Sharifah Khadijah AlHaddad, Mahfudzah Mohamed and Syed Musa AlHabshi - AlHaddad, Sharifah Khadijah; Mohamed, Mahfudzah; Alhabshi, Syed Musa (Faculty of Accountancy, 2004)
The academic achievement of Malaysian students being non-English proficient have long been a major national education concern in Malaysian in the last decade. This among other factors culminated in the recent change in the Malaysian national education policy on English as a medium of instruction for mathematics and science with immediate implementation at primary school level. The global concern is also affecting accounting education. The Education Committee of the International Federation of Accountants (IFAC) has been one of the few active international players on global accounting education. The assessment of professional competencies based on the whole range of knowledge, skills and professional values, is a determinant factor affecting accounting education. Communication, intellectual and interpersonal skills form part of the elements of accounting education and experience as per IFAC ED9. Proficiency in English, measured by students ability to effectively communicate to a certain extent, may have an influence on their ability to master the courses or programmes where English is the medium of instruction. The purpose of this preliminary study is to examine the academic performance of limited- English-proficient Universiti Teknologi MARA (UiTM)'s Bachelor of Accountancy (Hons) students (being non native speakers of English Language). A sample from archives on grades obtained was analyzed, employing historical data analysis (data mining technique). The findings of this study suggested that the relationship between English proficiency and accounting students' academic performance existed in the case of limited-English-proficient students.